Cytological Surveillance Management Pathways for Women with a Low-grade Abnormal Cervical Smear - Bhandari, Abhi (Université d'Ottawa / University of Ottawa, 2016)
A conservative strategy for women with a low-grade abnormal cervical smear is continued cytological surveillance by repeat Papinacolaou testing, but there is surprisingly little information on the management of such follow-up. Our objectives were to investigate such management pathways, their determinants, and psychological implications using data from the cytological surveillance arm of the Trial of Management of Borderline and Other Low-grade Abnormal cervical smears. A substantial proportion of participants had ongoing unresolved cytology at last follow-up (42.7%); a policy of following women solely though cytological surveillance to manage these women may be inefficient. A high-risk human papillomavirus test, smoking and age were significantly associated with the management pathways (p-value <0.05). While there were some limitations, our results were reassuring with respect to this group of women with ongoing unresolved cytology, since there were no differences in anxiety and depression scores across the management pathways after thirty months of follow-up.
Keywords: Cervical cancer screening; Cytological Surveillance; Pap test; TOMBOLA; HADS; Anxiety; Depression